Job Satisfaction of Teacher-Librarians: A Case Study of the Jaffna District, Sri Lanka - Visakaruban, M.; Navaneethakrishnan, S. (Chinese Librarianship: an International Electronic Journal, 2014)
The study shed light on the level of influence of various factors on the job satisfaction of teacher-librarians. The findings of this study shows that teacher-librarians working in the Jaffna District, Sri Lanka are more comfortable with their colleagues and more satisfied with job security, supervision, social relation to the work, decision-making authority, administration, opportunity for education, personal career growth, gaining respect for assigned duties, and management policy. However, recognition, promotion, salary, and working facilities are negatively influencing the job satisfaction of teacher-librarians.